To compare the outcome of intramedullary nailing and locking compression plate fixation in treatment of proximal one third tibia fracture: A randomized control trial - Siddharth Jain; Rahul Verma; Sanjeev Gaur; Ashish Gohiya (International Journal of Medical Research and Review, 2016)
Background: Fractures of tibia shaft are most common of long bone fractures. Proximal tibia fractures account for approximately 5% to 11% of all tibial injuries and affect knee function and stability in most of the cases. Higher rates of malunion and increased incidence of associated complications have made these fractures particularly problematic. In recent years due to advancement in technique, proximal tibia plating and multidirectional locked intramedullary nailing, both have become widely used treatment modalities for proximal tibial metaphyseal fractures. This study was performed to compare plating and nailing options in proximal tibia extra-articular fractures.Materials and methods: This randomized prospective clinical study was conducted on 62 skeletally mature patients with closed extra-articular fracture of the proximal tibia treated with proximal tibial locking compression plating (PTLCP) or intramedullary nailing (IMN) by expert surgeons at a tertiary trauma center.Results: Postoperative hospital stay (p = 0.043), postoperative infection rate (p = 0.036) were significantly high in the PTLCP group than in the IMN group, while rate of malunion (p=0.041) and nonunion(0.037) were significantly high in IMN group than in PTLCP group. However there was no clear advantage of either technique in terms of functional recovery of knee.Conclusion: Present comparison of IMN and PTLCP for the treatment of proximal one third tibia fracture showed no clear advantage of either technique. Present study concluded that both forms of treatment (IMN and PTLCP) provide adequate fracture stability. Level of evidence: Level 2, randomized controlled trial.